An experimental and theoretical approach to the molecular structure of 3-{[4-(3-Methyl-3-phenyl-cyclobutyl)-thiazol-2-yl]-hydrazono}-1,3-dihydro- indol-2-one - Saracoglu, Hanife; Cukurovali, Alaaddin (Wiley, 2012)
The title molecule, 3-{[4-(3-methyl-3-phenyl-cyclobutyl)-thiazol-2-yl]-hydrazono}-1,3-dihydro-indol-2-one (C22H20N4O1S1), was prepared and characterized by 1H NMR, 13C NMR, IR, UVvisible, and single-crystal X-ray diffraction. The compound crystallizes in the monoclinic space group P21 with a = 8.3401(5), b = 5.6976(3), c = 20.8155(14) angstrom, and beta = 95.144(5)degrees. Molecular geometry from X-ray experiment and vibrational frequencies of the title compound in the ground state has been calculated using the HartreeFock with 6-31G(d, p) and density functional method (B3LYP) with 6-31G(d, p) and 6-311G(d, p) basis sets, and compared with the experimental data. The calculated results show that optimized geometries can well reproduce the crystal structural parameters, and the theoretical vibrational frequencies values show good agreement with experimental data. Density functional theory calculations of the title compound and thermodynamic properties were performed at B3LYP/6-31G(d, p) level of theory. (c) 2011 Wiley Periodicals, Inc. Int J Quantum Chem, 2012
Keywords: hydrazone ligand; X-ray structure determination; IR spectra; DFT calculations; molecular electrostatic potential